Les alliances lydo-égyptienne et lydo-babylonienne - Kevin LELOUX (Akdeniz University, 2021)
This article analyses the credibility given to the alliances, which were supposedly formed by the king of Lydia Croesus with Amasis of Egypt and with Nabonidus king of Babylon. At the same time, the diplomatic relations of Amasis with Cyrene and with Polycrates of Samos are studied, as well as the connection between the Lydian Kingdom and Egypt. Further, this study focuses also on the diplomatic ties built by the king of Babylon in order to determine what was the nature of the links between him and Croesus.